Unbalanced and Balanced Acrocentric Rearrangements Involving Chromosomes Other Than Chromosome 21 at Amniocentesis - Chih-Ping Chen; Schu-Rern Chern; Pei-Chen Wu; Fuu-Jen Tsai; Chen-Chi Lee; Dai-Dyi Town; Wen-Lin Chen; Li-Feng Chen; Meng-Shan Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2009)
Objective: To investigate unbalanced and balanced acrocentric rearrangements involving chromosomes other than chromosome 21 at amniocentesis. Materials and Methods: From January 1987 to September 2009, 31,194 amniocenteses were performed at Mackay Memorial Hospital, Taipei, Taiwan. Two cases with unbalanced acrocentric rearrangements involving chromosomes other than chromosome 21 from two families, and 24 cases with balanced acrocentric rearrangements involving chromosomes other than chromosome 21 from 21 families were diagnosed and investigated. Results: We detected i(13q13q), +13 (one case), rob(13q14q), +13 (one case), rob(13q14q) (16 cases), rob(14q15q) (five cases), rob(13q15q) (one case), rob(15q22q) (one case), and mosaic rob(14q22q) (one case). Of the 25 cases that underwent parental cytogenetic investigation, six arose de novo and 19 were inherited (10 maternal and nine paternal). The 16 families with an inherited Robertsonian translocation included rob(13q14q) (11 families), rob(14q15q) (four families), and rob(15q22q) (one family). Of these 16 families, only two had known parental carrier status prior to the first amniocentesis, while the other 14 were aware of a parental carrier status only after prenatal diagnosis of a fetus with a heterologous Robertsonian translocation. The 18 fetuses with balanced heterologous Robertsonian translocations inherited them from six maternal carriers of rob(13q14q), four paternal carriers of rob(13q14q), four paternal carriers of rob(14q15q), and one maternal carrier of rob(15q22q). Neither UPD14 nor UPD15 was detected in any of the 16 cases tested for UPD. Conclusion: Concerning acrocentric rearrangements involving chromosomes other than chromosome 21, we found a frequency of 0.0064% for unbalanced rearrangements and 0.0769% for balanced rearrangements at amniocentesis in this study. rob(13q14q) was the most common and rob(14q15q) the second most common rearrangement. Of the families with an inherited translocation, 87.5% were aware of parental carrier status only after prenatal diagnosis of a fetus with a translocation by amniocentesis.